Analisi Pembiayaan Berbasis Bagi Hasil dan Rasio BOPO Pada Perbankan Syariah Di Indonesia - Wirman Wirman (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
The purpose of this study analyzes the factors that influence the financing volume-based profit-sharing and ROA ratio of the disclosure, the period January 2011 to December 2015. The dimensions were measured Third Party Fund (DPK) with an indication of the measurement scale ratio of the natural logarithm number of third party deposits, Profit by indications measurement scale ratio ROA, NPF (Non Performing Financing).The methodology used is panel da ta analysis using multiple linear regression. Of this study obtained a conclusion that the financing-sharing based on Islamic Banks (BUS) and Sharia influenced significantly by variable Third Party Funds (postitif / received), a variable profit (positive / received), the variable funding jammed / NPF ( Positive / received), variable Ratio ROA (positive / received), simultaneously Third Party Funds, Income and Rate NPF significant effect (positive / received). The financing-sharing based on Bank Financing Sharia significantly influenced by variables Third Party Funds (postitif / received), a variable profit (positive / received), the variable funding jammed / NPF (positive / received), variable Ratio ROA (positive / received), simultaneously Third Party Funds, Income, and NPF significant effect (positive / received).